RETRACTED: EEG signal processing by feature extraction and classification based on biomedical deep learning architecture with wireless communication - Sodagudi, Suhasini; Manda, Sridhar; Smitha, Bandi; Chaitanya, N.; Ahmed, Mohammed Altaf; Deb, Nabamita (Optik (Stuttgart), 2022)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of the Editor-in-Chief. Post-publication, an investigation conducted on behalf of the journal by Elsevier's Research Integrity & Publishing Ethics team discovered suspicious changes in authorship between the original submission and the revised version of this paper. During revision, the authors N Chaitanya, Mohammed Altaf Ahmed and Nabamita Deb were added to the revised paper without explanation and without exceptional approval by the journal editor, which is contrary to the journal policy on changes to authorship. Despite three emails, the authors did not provide an acceptable explanation to the authorship allegations. As such and due to the nature of the irregularities uncovered, the Editor has lost confidence in the validity/integrity and findings of the article and decided to retract the article. The scientific community takes a very strong view on this matter and apologies are offered to readers.